THE IMPORTANCE OF THE DRUG DOPROKIN - Axmedov Shamshod Jamshidovich (Лучшие интеллектуальные исследования, 2024)
Diseases of the gastrointestinal tract occupy a significant place in the general structure of somatic diseases throughout the world. The largest group of chronic diseases of the digestive organs are diseases of the organs of the gastroduodenal zone. In addition to functional diseases (functional dyspepsia occurs in 20% of the population), inflammatory and destructive diseases are common (gastroesophageal reflux disease - in almost 40% of the population, chronic gastritis and chronic duodenitis - in 45-50%, peptic ulcer disease of the stomach and duodenum - in 14 15 %).